Performance of Rocking Systems on Shallow Improved Sand: Shaking Table Testing - Tsatsis, Angelos; Anastasopoulos, Ioannis (Frontiers in Built Environment, 2015)
Recent studies have highlighted the potential benefits of inelastic foundation response during seismic shaking. According to an emerging seismic design scheme, termed rocking isolation, the foundation is intentionally under–designed to promote rocking and limit the inertia transmitted to the structure. Such reversal of capacity design may improve the seismic performance, drastically increasing the safety margins. However, the benefit comes at the expense of permanent settlement and rotation, which may threaten post-earthquake functionality. Such undesired deformation can be maintained within tolerable limits, provided that the safety factor against vertical loading FSV is adequately large. In such a case, the response is uplifting–dominated and the accumulation of settlement can be limited. However, this is not always feasible as the soil properties may not be ideal. Shallow soil improvement may offer a viable solution and is therefore worth investigating. Its efficiency is related to the nature of rocking, which tends to mobilize a shallow stress bulb. To this end, a series of shaking table tests are conducted, using an idealized slender bridge pier as conceptual prototype. Two systems are studied, both lying on a square foundation of width B. The first corresponds to a lightly-loaded and the second to a heavily-loaded structure. The two systems are first tested on poor and ideal soil conditions to demonstrate the necessity for soil improvement. Then, the efficiency of shallow soil improvement is studied by investigating their performance on soil crusts of depth z/B = 0.5 and 1. It is shown that a z/B = 1 dense sand crust is enough to achieve practically the same performance with the ideal case of dense sand. A shallower z/B = 0.5 improvement layer may also be considered, depending on design requirements. The efficiency of the soil improvement is ameliorated with the increase of rotation amplitude, and with the number of the cycles of the seismic motion.